Application of fractional sub-equation method to nonlinear evolution equations - Abdelkawy, Mohamed A. A.; El-Kalaawy, Omar H. H.; Al-Denari, Rasha B. B.; Biswas, Anjan (Nonlinear Analysis: Modelling and Control, 2018)
In this paper, we constructed a traveling wave solutions expressed by three types of functions, which are hyperbolic, trigonometric, and rational functions. By using a fractional sub-equation method for some space-time fractional nonlinear partial differential equations (FNPDE), which are considered models for different phenomena in natural and social sciences fields like engineering, physics, geology, etc. This method is a very effective and easy to investigate exact traveling wave solutions to FNPDE with the aid of the modified Riemann–Liouville derivative.